Concordance Test Between Dermoscopic and Histopathological Parameteres in Basal Cell Carcinoma - Felix Hartanto; Bagus Haryo Kusumaputra; Maylita Sari; Irmadita Citrashanty; Hasnikmah Mappamasing; Linda Astari; Willy Sandhika; Afif Nurul Hidayati; Cita Rosita Sigit Prakoeswa; Muhammad Yulianto Listiawan (Department of Dermatology and Venereology, Faculty of Medicine, Universitas Airlangga, 2024)
Background: Basal cell carcinoma (BCC) is the most common skin cancer and can cause local tissue damage. BCC can occur in all populations, regardless of skin color. Dermoscopy has compatibility with histopathology in determining the benign or malignant nature of a lesion. Dermoscopy can improve the diagnostic accuracy of BCC by >90%, with 7 parameters that can be found: arborizing vessels, blue-gray ovoid nests, blue-gray dots/globules, maple leaf-like areas, spoke-wheel areas, ulceration, and hiny white areas. Purpose: To assess the compatibility of each dermoscopy parameter with its corresponding histopathological parameters. Methods: Observational analytic study with a cross-sectional approach was performed. Dermoscopy parameters were obtained by reassessing all photographs, while histopathological parameters were obtained from pre-existing slide reviews. Cohen's Kappa test was performed to analyze both variables. Result: A Total of 26 samples met the inclusion criteria. Most BCCs were found in female sex (65.4%), age >50 years (80.8%), and facial location (88.5%). Cohen's Kappa test was significant in 2 out of 7 dermoscopy parameters: "blue-gray ovoid nests" (p = 0.0019; r = 0.458) and "spoke wheel areas" (p = 0.037; r = 0.371). The "shiny white areas" parameter could not be analyzed because there was no negative variation in the examination. The possibility of false positives and negatives could not be ruled out.  Conclusion: Significance between the two variables is found in 28.6% of the 7 parameters analyzed...